Postcommunism from within : social justice, mobilization, and hegemony - Kubik, Jan, 1953-; Linch, Amy (UPCC book collections on Project MUSE., 2013)
While the decline of communism in the late twentieth century brought democracy, political freedom, and better economic prospects for many people, it also produced massive social dislocation and engendered social problems that were far less pronounced under the old regimes. The fall of state socialism led to enormously complex political, economic, social, and cultural transformations, and while political liberalization was a lofty goal, it was neither uniform in its effects nor unqualified in its benefits. This book foregrounds the diversity of the historical experiences and the realities of people in the postcommunist region in examining how they are responding to these monumental changes at home.